2014
DOI: 10.1007/s10578-014-0445-7
|View full text |Cite
|
Sign up to set email alerts
|

Attributions for Parents’ Behavior by Boys With and Without Attention-Deficit/Hyperactivity Disorder

Abstract: Attributions for parents' behavior were examined in a sample of boys with and without Attention-Deficit/Hyperactivity Disorder (ADHD). Sixty-six boys (mean age = 9.75 years) rated attributions for their mothers' and their fathers' behavior, across positive and negative scenarios, and along four attribution dimensions (parent ability, parent effort, task difficulty, and child responsibility). Three-way interactions emerged among child ADHD status, parent gender, and attribution type, and among scenario valence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…However, contrary to our hypotheses, overall evidence for increased HAI in NDD was inconsistent. By contrast, there were indications that attributions of causality differed between CYP with and without NDD, as shown by increased globality of attributions in AS [61], or internality of attributions in CYP with ADHD [65].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, contrary to our hypotheses, overall evidence for increased HAI in NDD was inconsistent. By contrast, there were indications that attributions of causality differed between CYP with and without NDD, as shown by increased globality of attributions in AS [61], or internality of attributions in CYP with ADHD [65].…”
Section: Discussionmentioning
confidence: 83%
“…Adolescent girls with ADHD, recruited through a research summer camp, did not differ in HAI from female controls and, unlike controls, showed no association of HAI with aggression [64]. Likewise, boys with ADHD did not differ from controls in their external attributions of parental behaviour, but made more internal attributions to child responsibility [65]. Three gender-mixed studies that directly compared HAI between CYP with and without ADHD failed to find group differences for HAI [66][67][68].…”
Section: Interpretation Bias and Attention-deficit/ Hyperactivity Disordermentioning
confidence: 86%